Lefamulin in Patients with Community-Acquired Bacterial Pneumonia Caused by Atypical Respiratory Pathogens: Pooled Results from Two Phase 3 Trials - Susanne Paukner; David Mariano; Anita F. Das; Gregory J. Moran; Christian Sandrock; Ken B. Waites; Thomas M. File (MDPI AG, 2021)
Lefamulin was the first systemic pleuromutilin antibiotic approved for intravenous and oral use in adults with community-acquired bacterial pneumonia based on two phase 3 trials (Lefamulin Evaluation Against Pneumonia [LEAP]-1 and LEAP-2). This pooled analysis evaluated lefamulin efficacy and safety in adults with community-acquired bacterial pneumonia caused by atypical pathogens (Mycoplasma pneumoniae, Legionella pneumophila, and Chlamydia pneumoniae). In LEAP-1, participants received intravenous lefamulin 150 mg every 12 h for 5-7 days or moxifloxacin 400 mg every 24 h for 7 days, with optional intravenous-to-oral switch. In LEAP-2, participants received oral lefamulin 600 mg every 12 h for 5 days or moxifloxacin 400 mg every 24 h for 7 days. Primary outcomes were early clinical response at 96 ± 24 h after first dose and investigator assessment of clinical response at test of cure (5-10 days after last dose). Atypical pathogens were identified in 25.0% (91/364) of lefamulin-treated patients and 25.2% (87/345) of moxifloxacin-treated patients; most were identified by ≥1 standard diagnostic modality (M. pneumoniae 71.2% [52/73]; L. pneumophila 96.9% [63/65]; C. pneumoniae 79.3% [46/58]); the most common standard diagnostic modality was serology. In terms of disease severity, more than 90% of patients had CURB-65 (confusion of new onset, blood urea nitrogen > 19 mg/dL, respiratory rate ≥ 30 breaths/min, blood pressure <90 mm Hg systolic or ≤60 mm Hg diastolic, and age ≥ 65 years) scores of 0-2; approximately 50% of patients had PORT (Pneumonia Outcomes Research Team) risk class of III, and the remaining patients were more likely to have PORT risk class of II or IV versus V. In patients with atypical pathogens, early clinical response (lefamulin 84.4-96.6%; moxifloxacin 90.3-96.8%) and investigator assessment of clinical response at test of cure (lefamulin 74.1-89.7%; moxifloxacin 74.2-97.1%) were high and similar between arms. Treatment-emergent adverse event rates were similar in the lefamulin (34.1% [31/91]) and moxifloxacin (32.2% [28/87]) groups. Limitations to this analysis include its post hoc nature, the small numbers of patients infected with atypical pathogens, the possibility of PCR-based diagnostic methods to identify non-etiologically relevant pathogens, and the possibility that these findings may not be generalizable to all patients. Lefamulin as short-course empiric monotherapy, including 5-day oral therapy, was well tolerated in adults with community-acquired bacterial pneumonia and demonstrated high clinical response rates against atypical pathogens.